Patthanakan sangkhom Thai jak 6 Tula 2519 jon thueng 19 kunya 2549 : (Democracy Confederation)
'Evolution of Thailand from crisis 6 October 1976 to 19 September 2006 : Thailand is moving forward or moving backward? '